Is a Team Different from the Sum of its Parts? Evidence from Mutual Fund Managers - Bär, Michaela; Kempf, Alexander; Ruenzi, Stefan (Review of Finance, 2011)
Abstract This paper provides the first empirical test of the diversification of opinions theory and the group shift theory using real business data. Our data set covers management teams and single managers of US equity mutual funds. Our results reject the group shift theory and support the diversification of opinions theory: teams follow less extreme investment styles, their portfolios are less industry concentrated, and they are eventually less likely to achieve extreme performance outcomes. These results hold after taking into account the impact of fund and family characteristics as well as manager characteristics.